2021
DOI: 10.3390/molecules26134074
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Deferiprone–Resveratrol Hybrid as an Effective Lipophilic Anti-Plasmodial Agent

Abstract: Malaria i a serious health problem caused by Plasmodium spp. that can be treated by an anti-folate pyrimethamine (PYR) drug. Deferiprone (DFP) is an oral iron chelator used for the treatment of iron overload and has been recognized for its potential anti-malarial activity. Deferiprone–resveratrol hybrids (DFP-RVT) have been synthesized to present therapeutic efficacy at a level which is superior to DFP. We have focused on determining the lipophilicity, toxicity and inhibitory effects on P. falciparum growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…Licochalcone A inhibits P. falciparum mitochondrial complexes II and III, and possibly the erythrocyte membrane [33,34]. In this study, the tested iron chelators showed modest antimalarial activity, similar to previous reports [15,16,18,35]. No differences in sensitivity to DHA were observed among the parasites tested, although it should be noted that the ART resistance phenotype manifested in k13 mutants is not detectable by the growth inhibition assay employed in this study [5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Licochalcone A inhibits P. falciparum mitochondrial complexes II and III, and possibly the erythrocyte membrane [33,34]. In this study, the tested iron chelators showed modest antimalarial activity, similar to previous reports [15,16,18,35]. No differences in sensitivity to DHA were observed among the parasites tested, although it should be noted that the ART resistance phenotype manifested in k13 mutants is not detectable by the growth inhibition assay employed in this study [5].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to Fd, iron is a cofactor for enzymes such as aconitase, oxidoreductases, and ribonucleotide reductase. Moreover, hemoglobin, myoglobin, and cytochromes contain an iron- [15][16][17][18][19][20]. Some antimalarial drugs, such as quinine, mefloquine, and artesunate are antagonized by DFP [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ability of drugs to withhold iron from malarial parasites is a critical point for this suggested treatment [ 35 ]. We have previously reported that DFP-RVT exhibited greater lipophilicity and higher efficiency in the protection of β1-42 peptide aggregation in lipid-rich neuronal cells and the inhibition of cultured P. falciparum growth than DFP [ 16 , 23 ]. In addition, the iron-chelating activity (pFe) of DFP-RVT was found to be stronger than DFP (pFe(III) = 19.6 and 20.6, respectively) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, iron chelators withhold available iron from malarial parasites and subsequently inhibit parasite growth; therefore, they could potentially be candidates for adjuctive anti-malarial drugs in the treatment of malaria infections. Importantly, many iron chelators, such as deferoxamine (DFO), deferiprone (DFP), deferasirox (DFX), alkylthiocarbamates, 8-hydroxyquinoline, synthetic ferrichromes, FR160 catechol, 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) and deferiprone-resveratrol (DFP-RVT) hybrid, have been administered in the treatment of P. falciparum -infected RBC (PRBC), while P. bergheir - and P. vinckei -infected mice have exhibited effective anti-plasmodium agents [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation